Private Law Responses to Domestic Violence: The Intersection of Family Law and Tort - Kelly, Fiona (The Supreme Court Law Review, 2009)
This paper explores the progressive possibilities presented by two areas of private law – family law and tort law – in achieving economic justice for women who have been victims of domestic violence. The author first considers the role spousal support law might play in providing economic redress following abuse. While the Supreme Court of Canada’s decision in Leskun v. Leskun suggests that a court might consider the consequences of spousal misconduct when making a support order, courts remain reluctant to use support awards to address the economic impact of abuse. By contrast, tort law may appear to provide a more responsive framework for battered women. Women may use the tort of battery to seek damages to compensate for direct financial impact of the violence (e.g. medical expenses) and for indirect economic harm (e.g diminished employability). However, the challenges inherent in bringing a successful tort action mean that women rarely succeed in achieving compensation. The author concludes by considering other options (e.g. a public compensation scheme) which may be a solution for women seeking financial compensation for the harms suffered at the hands of a violent spouse.